KUALITAS BUTIR SOAL BUATAN GURU-GURU SMP MATA PELAJARAN MATEMATIKA DAN IPA DI KABUPATEN SUMENEP - Suparji, (Pendidikan Dasar, 2010)
Abstract: The study aims to know the quality of SMP teacher-made tests of math and science. Following level of difficulty, the result shows that it is 1) 21.25, 16.15 and 62.7% for math and; 2) 28.2%, 25.9% and 45.9%  for science successively. In terms of discriminating power it is 3) 3,7%, 7,8%, 12% and 76,5% for math and; 4) 7,7%, 13,2%, 18,2% and 60,9% for science successively. Meanwhile, the aitem total correlation shows 5) 6,5%, 50,7% and 42,8% for math and ; 6) 18,2%, 27,3% and 54,5% for science. Finally the reliability is only 20 % for math items and 10% for science.